2004
DOI: 10.1080/13816810490498305
|View full text |Cite
|
Sign up to set email alerts
|

Association of EFEMP1 with malattia leventinese and age-related macular degeneration: a mini-review

Abstract: Malattia leventinese (ML) or Doyne honeycomb retinal dystrophy (DHRD) was the first clinically and histopathologically described Mendelian maculopathy. The gene responsible for ML/DHRD, EFEMPI (fibulin-3/SI-5/FBNL) encodes a member of the fibulin family, a newly recognized family of extracellular matrix proteins. EFEMPImutations have not been found in age-related macular degeneration (AMD) patients despite the close phenotypic similarities between ML/DHRD and AMD. This non-correlating genotype/phenotype relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 39 publications
0
35
0
3
Order By: Relevance
“…This subsequently resulted in the association of FBLN5 with AMD (Stone et al 2004). Recently it has been suggested that similar pathological processes may be present in both AMD and EFEMP1 (Marmorstein 2004).…”
Section: Malattia Leventinesementioning
confidence: 97%
“…This subsequently resulted in the association of FBLN5 with AMD (Stone et al 2004). Recently it has been suggested that similar pathological processes may be present in both AMD and EFEMP1 (Marmorstein 2004).…”
Section: Malattia Leventinesementioning
confidence: 97%
“…The inexorable forward march of human genetics has revealed that this condition is due to a defect in the EFEMP-1 (fibulin3), in which there is an aminoacid substitution of arginine for trytophan at position 345. [72][73][74] Fibulin3 is one of a family of proteins present in basement membranes and elastic extracellular matrix such as the Bruch's membrane and the choroid of the eye. They appear to operate an organizational role in the supramolecular structure and matrix arrangement of well-recognized basement membrane proteins such as tropoelastin, fibronectin, fibrillin, and especially proteoglycans.…”
Section: Is There Anything Special About Ocular Immune Privilege?mentioning
confidence: 99%
“…A single mutation in the EFEMP1 (FIBL3) gene has been identified as causal in ML; 26 however, no reliably disease-associated EFEMP1 variants have been identified in AMD, despite some clinical resemblance of the two phenotypes. 27,28 One study has reported an association between the presence of cuticular drusen and rare missense mutations in the FIBL5 gene. 29 The hypothesis that extracellular matrix modifications due to variants in fibulin genes will generate disturbances on the RPE/Bruch's membrane interface and, subsequently, contribute to the development of AMD, is a plausible model for the disorder.…”
Section: Discussionmentioning
confidence: 99%